2010
DOI: 10.1111/j.1442-9993.2010.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbats in a ‘leafy’ urban landscape: are they persisting, and what factors influence their presence?

Abstract: Urbanization is an extreme form of habitat modification, but retention of native vegetation in bushland reserves may improve the ecological sustainability of cities. We focused on bats (Microchiroptera) and investigated the use of the urban matrix and surrounding bushland in a region of Sydney, Australia, where remnant bushland persists and gardens often support large trees. Ultrasonic surveys were conducted at 40 sites over one summer season in the backyard matrix, bushland remnants and surrounding National P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 69 publications
(110 reference statements)
2
43
2
Order By: Relevance
“…A positive effect of forest patch size on urban biodiversity has been previously found [40][41][42][43]. Our study supports previous findings associated with species-area relationships [44] in urban and in peri-urban landscapes.…”
Section: Factors Affecting Bird Species Richness In Upufssupporting
confidence: 82%
“…A positive effect of forest patch size on urban biodiversity has been previously found [40][41][42][43]. Our study supports previous findings associated with species-area relationships [44] in urban and in peri-urban landscapes.…”
Section: Factors Affecting Bird Species Richness In Upufssupporting
confidence: 82%
“…Species-area relationships, with fewer species in smaller sites, have been observed for microbes (Green et al, 2004;Horner-Devine et al, 2004;Bell et al, 2005) in habitats such as tree holes owing to the greater potential for colonization and quantity and diversity of available resources and habitats. At least for macroorganisms, urban, habitat area has a positive influence on biodiversity (Basham et al, 2010;Shanahan et al, 2011;Beninde et al, 2015). If urban habitat patches act analogously to tree holes, we expect to find fewer microbial species in smaller habitats in cities.…”
Section: Introductionmentioning
confidence: 99%
“…Basham et al (2011) reported lower bat activity in well-vegetated protected areas compared with less-vegetated urban areas in the Sydney region of eastern Australia, and suggested that the confounding effects of soil fertility on vegetation extent-a legacy of non-random clearing-may be responsible for this result. Looney et al (2009) proposed that biases in clearing leading to a negative association between remnant area and soil fertility underpinned the lack of relationship between grassland beetle community structure and patch size in prairie remnants in a heavily modified agricultural matrix in the north-western United States.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Several of these studies (Januchowski et al 2008;Looney et al 2009;Basham et al 2011) highlighted that a lack of an area effect was due to biased vegetation clearing patterns, whereby soil fertility/productivity was negatively correlated with habitat area. Because bigger remnants were associated with poorer quality soils, a positive effect of area on the response variable in these studies was not realised.…”
Section: Exponentmentioning
confidence: 97%